DEGRADABILITAS BAHAN KERING, BAHAN ORGANIK DAN SERAT KASAR RANSUM DENGAN BERBAGAI LEVEL BAGASSE SECARA IN SACCO - Noorsatiti, Mahaken Novis; Nuswantara, Limbang Kustiawan; Subrata, Agung (Animal Agriculture Journal, 2012)
This research was conducted to determine in sacco degradability of dry matter, organic matter and crude fiber in ration with different levels of bagasse and determine the best level of bagasse in ruminant ration from degradability. The research is expected to give information about the best level of bagasse as a source of crude fiber in the complete feed views of degradability of dry matter, organic matter and crude fiber. Research conducted at the Laboratory of Animal Feed Faculty of Animal Husbandry and Agriculture Diponegoro University Semarang from October 2011 to February 2012.The research was conducted by using a three Jawa Randu Goat which fistulated on rumen as replication. The treatment are T1 = ration level of 25% bagasse, T2 = bagasse rations with 30% level, T3 = ration with the level of 35% bagasse and T4 = bagasse rations with 40% level. Ration degradability measured by using in Sacco method. The variables measured were percent loss of DM, OM and CF to calculate the fraction of a, b, c and degradation theory (DT) dry matter, organic matter and crude fiber. To calculate the degradation of feed at a time "t" (DT) used the exponential equation P = a + b (1 – exp-ct). Fraction of the value of a, b, c and DT were then analyzed statistically based on completely randomized design (CRD) if there is a treatment effect, followed by Duncan's Multiple Range Test (DMRT) for difference between means.The analysis of variance showed that there was significant effect (P <0.05) between the fraction of easily degradable (a) DM, OM and CF, and degradation theory (DT) DM, OM and CF, therefore the potentially degradable fraction (b) DM, OM and CF, the degradation rate of potentially degradable fraction (c) DM, OM and CF showed no real difference.Keywords: degradability, dry matter, organic matter, crude fiber